2019
DOI: 10.20944/preprints201911.0076.v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploring Mammalian Genome within Phase-Separated Nuclear Bodies: Experimental Methods and Implications for Gene Expression

Abstract: The importance of genome organization at the supranucleosomal scale in the control of gene expression is increasingly recognized today. In mammals, Topologically Associating Domains (TADs) and the active / inactive chromosomal compartments are two of the main nuclear structures that contribute to this organization level. However, recent works reviewed here indicate that, at specific loci, chromatin interactions with nuclear bodies could also be crucial to regulate genome functions, in particular transcription.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…To investigate the role played by LLPS in spatial genome organization, we used human HeLa cells that were treated with 1,6-HD. This aliphatic alcohol is predicted to disrupt weak hydrophobic interactions, both in vitro and in vivo , disassembling LLPS-dependent macromolecular condensates ( 61–63 ). Molecular condensates depended purely on phase separation driven by electrostatic interactions are expected to be unaffected by 1,6-HD treatment ( 61 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the role played by LLPS in spatial genome organization, we used human HeLa cells that were treated with 1,6-HD. This aliphatic alcohol is predicted to disrupt weak hydrophobic interactions, both in vitro and in vivo , disassembling LLPS-dependent macromolecular condensates ( 61–63 ). Molecular condensates depended purely on phase separation driven by electrostatic interactions are expected to be unaffected by 1,6-HD treatment ( 61 ).…”
Section: Resultsmentioning
confidence: 99%
“…This aliphatic alcohol is predicted to disrupt weak hydrophobic interactions, both in vitro and in vivo , disassembling LLPS-dependent macromolecular condensates ( 61–63 ). Molecular condensates depended purely on phase separation driven by electrostatic interactions are expected to be unaffected by 1,6-HD treatment ( 61 ). Nevertheless, 1,6-HD is the only available tool to test in vivo the contribution of LLPS in the assembly of macromolecular complexes at this moment ( 63 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies reported the existence of enhancer hubs: spatially-localized clusters containing multiple enhancers 27,28,31 that may facilitate transcriptional activation by creating a local microenvironment whereby transcriptional resources are shared, akin to early models of 'transcription hubs' 79 . Formation of enhancer hubs may require interactions between components of the transcriptional machinery which could contribute, or result from, the assembly of phase-separated condensates 30,35,36,[80][81][82] . In this model, enhancers need not directly touch their target promoters but merely come into close proximity 24,83 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to obtain further insights into the nature of the chemical interactions underlying assembly of insulator proteins, we looked at the effect of 1,6-hexanediol (1,6-HD) on insulator bodies. 1,6-HD is an agent that perturbs hydrophobicity-dependent LLPS condensates presumably through disruption of weak hydrophobic interactions (41, 74, 75). In addition, unlike LLPS entities like the nucleolus (76) and transcription condensates (77), solid aggregates such as viral replication compartments (78), the cytoskeleton(74) and tetO binding (79) are largely resistant to 1,6-HD.…”
Section: Resultsmentioning
confidence: 99%